ATTENTION: DOCKET 29044 - MOTT,DR (Tufts Archival Research Center, 2007)
Letter from the Association of Flight Attendants to the Civil Aeronautics Board regarding a proposed ban on smoking on certain flights. Includes the stipulations that smoke alarms must be installed in all bathrooms and confined spaces, heavy fines must be levied against people who ignore the rules and competent air filters must be installed on every plane with smoking.